Relasi Media-Negara-Masyarakat dan Pasar dalam Era Reformasi - Hermin Indah Wahyuni (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2000)
The withdrawal of state domination does not necessarily lead to the institutionalization of market. Freedom of information also requires a new kind of societal conduct. Indonesia currcntly faces tension in settling a triangular relationship between state, market and the society